Prediction for blood lactate during exercise using an artificial intelligence—Enabled electrocardiogram: a feasibility study - Huang, Shu-Chun; Lee, Chen-Hung; Hsu, Chih-Chin; Chang, Sing-Ya; Chen, Yu-An; Chiu, Chien-Hung; Hsiao, Ching-Chung; Su, Hong-Ren (Frontiers in Physiology, 2023)
The acquisition of blood lactate concentration (BLC) during exercise is beneficial for endurance training, yet a convenient method to measure it remains unavailable. BLC and electrocardiogram (ECG) both exhibit variations with changes in exercise intensity and duration. In this study, we hypothesized that BLC during exercise can be predicted using ECG data. Thirty-one healthy participants underwent four cardiopulmonary exercise tests, including one incremental test and three constant work rate (CWR) tests at low, moderate, and high intensity. Venous blood samples were obtained immediately after each CWR test to measure BLC. A mathematical model was constructed using 31 trios of CWR tests, which utilized a residual network combined with long short-term memory to analyze every beat of lead II ECG waveform as 2D images. An artificial neural network was used to analyze variables such as the RR interval, age, sex, and body mass index. The results demonstrated that the standard deviation of the fitting error was 0.12 mmol/L for low and moderate intensities, and 0.19 mmol/L for high intensity.Weighting analysis demonstrated that ECG data, including every beat of ECG waveform and RR interval, contribute predominantly. By employing 2D convolution and artificial neural network-based methods, BLC during exercise can be accurately estimated non-invasively using ECG data, which has potential applications in exercise training.